Morphological analysis of the urethral muscle of the male pig with relevance to urinary continence and micturition. Issue 3 (17th November 2015) - Ragionieri, Luisa; Ravanetti, Francesca; Gazza, Ferdinando; Botti, Maddalena; Ivanovska, Ana; Cacchioli, Antonio
Abstract: To investigate whether the pig could be considered a suitable model to study lower urinary tract function and dysfunction, the pelvic urethra of 24 slaughtered male pigs were collected, and the associated muscles were macroscopically, histologically and histochemically analyzed. In cross‐sections of the urethra, a muscular complex composed of an inner layer of smooth muscle and an outer layer of striated muscle that are not separated by fascial planes was observed. A tunica muscularis, composed of differently oriented smooth muscle bundles, is only evident in the proximal part of the pelvic urethra while, in the remaining part, it contributes to form the prostatic fibromuscular stroma. The striated urethral muscle surrounds the pelvic urethra in a horseshoe‐like configuration with a dorsal longitudinal raphe, extending from the bladder neck to the central tendon of perineum. Proximally to the bladder, it is constituted of slow‐twitch and fast‐twitch myofibers of very small diameter, and embedded in an abundant collagen and elastic fiber net. Moving caudally it is gradually encircled and then completely substituted by larger and compact myofibers, principally presenting circular orientation and fast‐twitch histochemical characteristics. So, like in humans, the cranial tract of the muscular system surrounding the pelvic urethra is principally composed of smooth musculature. The striated component cranially may have a role in blocking retrograde ejaculation, while the middle and caudal tracts may facilitate urine and semen flow, and seem especially concerned with the rapid and forceful urethral closure during active continence. Some differences in the morphology and structure between pigs and humans seem due to the different morphology of the 'secondary' sexual organs that develop from the urethral wall and to the different effect of gravity on the mechanics of the urinary system in quadruped and bipedal mammals.